2017
DOI: 10.1093/jxb/erx187
|View full text |Cite
|
Sign up to set email alerts
|

Citrus CitNAC62 cooperates with CitWRKY1 to participate in citric acid degradation via up-regulation of CitAco3

Abstract: Two novel transcription factors, CitNAC62 and CitWRKY1, were involved in citric acid degradation in citrus fruit, potentially via enhanced expression of CitAco3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 38 publications
0
50
0
Order By: Relevance
“…However, NAC transcription factors may have different subcellular locations; for example. banana MaNAC1‐ 5 is located in the nucleus and MaNAC2 in the nucleus and cytoplasm (Shan et al , ), and citrus CitNAC62 is located in the cytoplasm (Li et al , ) even with nuclear localization signal (NLS). AdNAC6/7 also have NLS at their C‐terminal ends (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, NAC transcription factors may have different subcellular locations; for example. banana MaNAC1‐ 5 is located in the nucleus and MaNAC2 in the nucleus and cytoplasm (Shan et al , ), and citrus CitNAC62 is located in the cytoplasm (Li et al , ) even with nuclear localization signal (NLS). AdNAC6/7 also have NLS at their C‐terminal ends (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…banana MaNAC1-5 is located in the nucleus and MaNAC2 in the nucleus and cytoplasm (Shan et al, 2012), and citrus CitNAC62 is located in the cytoplasm (Li et al, 2017a) even with nuclear localization signal (NLS). However, NAC transcription factors may have different subcellular locations; for example.…”
Section: Researchmentioning
confidence: 99%
“…The DUALhunter system (Dualsystems Biotech) was used to investigate the interaction between FaERF#9 and FaMYB98. Full-length coding sequences of FaERF#9 and FaMYB98 were cloned into pDHB1 bait vector and pPR3-N prey vector, respectively, sequences were verified, and the bait plasmid was cotransformed with prey plasmid into NMY51 in the following combinations: FaMYB98-pDHB1/pPR3-N, FaMYB98-pDHB1/FaERF#9-pPR3-N, Fa-MYB98-pDHB1/pOst1-NubI, FaERF#9-pDHB1/pPR3-N, FaERF#9-pDHB1/ FaMYB98-pPR3-N, and FaERF#9-pDHB1/pOst1-NubI (Li et al, 2017a). Transformed cells were spread onto the following plates: DDO (SD medium-Trp-Leu), QDO (SD medium-Trp-Leu-His-Ade), and QDO+3-AT (QDO medium supplemented with 1 mm 3-amino-1,2,4-triazole).…”
Section: Yeast Two-hybrid Assaymentioning
confidence: 99%
“…Malate accumulation involves transcriptional regulation of vacuolar proton pumps and malate transporters (Xie et al, 2012; Li et al, 2017; Hu et al, 2017). It has been reported that MdbHLH3 plays a central role in the accumulation of both malate and anthocyanins by interacting with MdMYB1 and binding to the promoter of MdMYB1 (Xie et al, 2012; Hu et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%